Sex differences in hospitalized adult patients with cellulitis: A prospective, multicenter study. (March 2021) - Collazos, Julio; de la Fuente, Belén; de la Fuente, Javier; García, Alicia; Gómez, Helena; Rivas-Carmenado, María; Suárez-Zarracina, Tomás; García-Carús, Enrique; Suárez-Diaz, Silvia; Enríquez, Héctor; Sánchez, Paula; Alonso, María; et al.
Highlights: Adult female patients with cellulitis were substantially older than adult male patients. Female patients had higher rates of edema/lymphedema as an underlying condition than male patients. Female patients were more likely to have had prior episodes of cellulitis than male patients. Male patients with cellulitis were more likely to have positive pus cultures than female patients. The location of cellulitis involvement differed between the sexes. Abstract: Objectives: Sex differences in adult cellulitis, a frequent cause of hospitalization, have not been analyzed. These differences were investigated in a large cellulitis series. Methods: This was a prospective observational study of 606 Spanish hospitalized cellulitis patients. Different comorbidities, clinical, diagnostic, and treatment data were compared between the sexes. Multiple logistic regression modeling was performed to determine the variables independently associated with sex. Results: Overall 606 adult cellulitis patients were enrolled; 314 (51.8%) were male and 292 (48.2%) were female. Females were older (mean age 68.8 vs 58.9 years, p < 0.0001), less likely to have prior wounds ( p = 0.02), and more likely to have venous insufficiency ( p = 0.0002) and edema/lymphedema ( p = 0.0003) than males. The location of the infection differed between the sexes ( p = 0.02). Males were more likely to have positive pus cultures ( p = 0.0008), the causing agent identified ( p = 0.04), and higher rates of Staphylococcus aureus infection ( p = 0.04) and received longer antibiotic treatment ( p = 0.03). Factors independently associated with female sex in the multivariate analysis were older age ( p < 0.0001), prior cellulitis ( p = 0.01), presence of edema/lymphedema as the predisposing factor ( p = 0.004), negative versus positive pus culture ( p = 0.0002), and location of cellulitis other than in the lower extremities ( p = 0.035). Conclusions: Differences between male and female patients with cellulitis were age, recurrence, presence of edema/lymphedema, positivity of pus culture, and topography of the infection.